Nickel-iron-aluminum coprecipitation catalyst, preparation method and application thereof, and mercaptan thioetherification method
Through the hydrogen-programmed temperature-raising reduction treatment of the nickel-ferro-aluminum co-precipitation catalyst, the problem of insufficient activity and stability of the catalyst when cracking gasoline thiol is solved, and the efficient thiol thiol thiol is achieved, which extends the life of the catalyst and Improved desulfurization efficiency.
Patent Information
- Application Number
- CN202310777917.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-03
Smart Images

Figure CN119236940A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nickel-iron-aluminum coprecipitation catalyst, a preparation method and application thereof, and a mercaptan thioetherification method. Background Art
[0002] In recent years, global crude oil prices have remained high, ethylene production capacity has grown rapidly, and aromatics demand has been strong. The diversification, heaviness, and inferiority of cracking raw materials have become the norm, which will inevitably lead to excessive impurities in cracking gasoline, especially organic sulfur, affecting the activity and life of traditional catalysts.
[0003] In the field of deep desulfurization of gasoline and diesel, new process technologies for producing ultra-low sulfur gasoline have been developed abroad. Among them, the CDHydro&CDHDS process developed by CDTECH in the United States and the PrimeG+ process developed by Axens in France have broad application prospects. These two processes are to react the diolefins and mercaptans in catalytic cracking gasoline (FCCG) with sulfide under mild operating conditions through the action of catalysts to form high-boiling sulfides, and then enter the heavy gasoline component (HCN) in the subsequent fractionation unit to obtain sulfur-free and olefin-rich light gasoline (LCN), which not only avoids the octane loss caused by the olefin saturation reaction of LCN directly entering the hydrodesulfurization unit, but also generates monoolefins through selective hydrogenation in this reaction process. This treatment process can remove mercaptans and diolefins in gasoline at the same time. The process combining thioetherification technology with hydrodesulfurization has the characteristics of high gasoline desulfurization rate, low olefin saturation rate and high octane number. The sulfur-rich, diene-free HCN separated after thioetherification treatment is subjected to hydrodesulfurization treatment, which can improve the stability and life of the catalyst and extend the operation cycle of the device.
[0004] At present, foreign research on this technology is mainly focused on the process, and there is still no special report on the catalyst used for the thioetherification reaction. The catalyst used is mainly commercial Ni and Pd hydrogenation catalysts, which have high catalytic activity for diene hydrogenation and thioetherification reactions. CN102125846B discloses a mercaptan etherification catalyst, which uses an alumina carrier modified with 0.1wt%-20wt% of metal oxides, loaded with 5wt%-40wt% Fe and / or Ni oxides, and / or 1wt%-10wt% Mo oxides, for removing mercaptans and dienes from full-fraction catalytic cracking gasoline.
[0005] CN102140363A discloses a method for gasoline etherification and alkylation desulfurization, which uses a solid phosphoric acid catalyst with SiO2-Al2O3 or SiO2-ZrO2 as a carrier. The transfer rate of mercaptans and thiophenes in this method reaches more than 90%. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem of removing mercaptans toxic to a first-stage catalyst in a cracked gasoline raw material in the prior art, and to provide a nickel-iron-aluminum coprecipitation catalyst and a preparation method and application thereof, and a mercaptan thioetherification method. The catalyst has a low hydrogen-programmed temperature reduction temperature and has the advantages of high activity and good stability for mercaptan thioetherification.
[0007] In order to achieve the above object, the present invention provides a nickel-iron-aluminum co-precipitation catalyst in a first aspect, the catalyst comprising the following components:
[0008] Iron and / or iron oxides, nickel and / or nickel oxides, aluminum and / or aluminum oxides;
[0009] In terms of element molar ratio, the molar ratio of nickel to aluminum is 0.2-5:1; the molar ratio of iron to aluminum is 0.2-5:1;
[0010] The hydrogen-programmed temperature reduction temperature of the catalyst is 250-440°C.
[0011] A second aspect of the present invention provides a method for preparing the catalyst of the present invention, the method comprising:
[0012] The aqueous solution I containing alkaline substances is contacted with the solution II containing nickel source, iron source and aluminum source to obtain precipitation, and the precipitation is obtained by separation, washing and drying; and the precipitation is roasted.
[0013] The third aspect of the present invention provides a use of the catalyst of the present invention in the thioetherification of mercaptans.
[0014] A fourth aspect of the present invention provides a method for thioetherification of mercaptans, the method comprising:
[0015] (1) sulfiding the mercaptan thioetherification catalyst under sulfiding conditions;
[0016] (2) contacting the mercaptan-containing raw material with a sulfurized mercaptan thioetherification catalyst;
[0017] The mercaptan thioetherification catalyst contains the nickel-iron-aluminum co-precipitation catalyst of the present invention.
[0018] Through the above technical scheme, the nickel-iron-aluminum coprecipitation catalyst of the present invention has a hydrogen-programmed temperature reduction temperature of 250-440° C., and the hydrogen-programmed temperature reduction temperature is low. The nickel-iron-aluminum coprecipitation catalyst has the advantages of high activity and good stability for mercaptan thioetherification. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a hydrogen-programmed temperature reduction temperature curve of the catalyst prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] The first aspect of the present invention provides a nickel-iron-aluminum co-precipitation catalyst, which comprises the following components:
[0022] Iron and / or iron oxides, nickel and / or nickel oxides, aluminum and / or aluminum oxides;
[0023] In terms of element molar ratio, the molar ratio of nickel to aluminum is 0.2-5:1; the molar ratio of iron to aluminum is 0.2-5:1;
[0024] The hydrogen-programmed temperature reduction temperature of the catalyst is 250-440°C.
[0025] According to a preferred embodiment of the present invention, the hydrogen-programmed temperature reduction temperature of the catalyst is 300-440°C, preferably 370-420°C.
[0026] According to a preferred embodiment of the present invention, the molar ratio of nickel to aluminum is 0.5-2:1, calculated on the molar ratio of elements. For example, the molar ratio of nickel to aluminum can be 0.5:1, 0.6:, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1.
[0027] According to a preferred embodiment of the present invention, the molar ratio of iron to aluminum is 0.5-2:1, calculated as the molar ratio of elements. For example, the molar ratio of iron to aluminum can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1.
[0028] According to a preferred embodiment of the present invention, the catalyst particle size distribution is 2nm-10nm.
[0029] According to a preferred embodiment of the present invention, the catalyst further contains manganese and / or manganese oxide; preferably, in terms of element molar ratio, the molar ratio of manganese to aluminum is 0.1-2:1, for example, the molar ratio of manganese to aluminum can be 0.5:1, 0.6:, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1, preferably 0.1-1:1.
[0030] The iron-based catalysts having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to a preferred embodiment of the present invention, the present invention provides a method for preparing the catalyst of the present invention, which comprises:
[0031] The aqueous solution I containing alkaline substances is contacted with the solution II containing nickel source, iron source and aluminum source to obtain precipitation, and the precipitation is obtained by separation, washing and drying; and the precipitation is roasted.
[0032] In the present invention, the alkaline substance can be selected from a wide range. According to a preferred embodiment of the present invention, the alkaline substance is selected from at least one of sodium bicarbonate, ammonium bicarbonate, sodium hydroxide and ammonia water, preferably at least one of sodium bicarbonate and ammonium bicarbonate.
[0033] In the present invention, there is no particular limitation on the nickel source as long as it is soluble in water. According to a preferred embodiment of the present invention, the nickel source is selected from at least one soluble salt of nickel; the soluble salt of nickel may be, for example, nickel nitrate, nickel acetate, nickel sulfate, nickel carbonate, etc.
[0034] In the present invention, there is no particular limitation on the iron source as long as it is soluble in water. According to a preferred embodiment of the present invention, the iron source is selected from at least one soluble salt of iron; the soluble salt of iron may be, for example, ferric nitrate, ferric sulfate, ferric chloride, iron sulfide, etc.
[0035] In the present invention, there is no particular limitation on the aluminum source, as long as it is soluble in water. According to a preferred embodiment of the present invention, the aluminum source is selected from at least one of soluble aluminum salts. The soluble aluminum salt may be, for example, aluminum nitrate, aluminum sulfate, aluminum chloride, sodium aluminate, aluminum hydroxide, and the like.
[0036] In the present invention, the concentration of the alkaline substance in the aqueous solution I can be selected in a wide range. According to a preferred embodiment of the present invention, the concentration of the alkaline substance is 0.1-2 mol / L, preferably 0.8-2 mol / L.
[0037] In the present invention, in solution II, the concentration of the aluminum source can be selected in a wide range. According to a preferred embodiment of the present invention, the aluminum source is calculated as aluminum element, and the concentration of the aluminum element is 0.1-3 mol / L.
[0038] In the present invention, in solution II, the range of solvents available for selection is relatively wide. According to a preferred embodiment of the present invention, the solvent is selected from at least one of water, ethylene glycol, ethanol and polyethylene glycol, preferably ethylene glycol.
[0039] In the present invention, the contact conditions have a wide range of optional contact conditions. According to a preferred embodiment of the present invention, the contact conditions include: a temperature of 30-100°C, preferably 40-80°C; the contact time can be reasonably determined according to actual needs, preferably 40min-6h, preferably 1h-5h.
[0040] In the present invention, there is no particular limitation on the washing conditions, as long as the impurities on the surface of the precipitate can be removed, for example, washing with deionized water for 2-5 times.
[0041] In the present invention, the drying conditions can be selected in a wide range. According to a preferred embodiment of the present invention, the drying conditions include: a temperature of 80-150°C, preferably 110-140°C; the drying time can be reasonably determined according to actual needs, and the preferred time is 2-6h.
[0042] In the present invention, the range of roasting conditions is relatively wide. According to a preferred embodiment of the present invention, the roasting conditions include: a temperature of 300-600° C., and the roasting time can be reasonably determined according to actual needs, preferably 2-6 hours.
[0043] According to a preferred embodiment of the present invention, the aqueous solution I is added to the solution II at a rate of 0.2-10 ml / min.
[0044] According to a preferred embodiment of the present invention, the method for preparing the catalyst further comprises:
[0045] The solution III containing the manganese source, the aqueous solution I and the solution II are contacted to obtain a precipitate, and the precipitate is separated, washed and dried to obtain the precipitate; the precipitate is roasted; preferably, the manganese source is selected from at least one of the soluble salts of manganese.
[0046] In the present invention, the contacting method can be as follows: after mixing solution II and solution III, add solution I to contact to obtain precipitation; or solution I, solution II, and solution III are contacted in parallel to obtain precipitation; or solution III and solution I are added in parallel to solution II to contact to obtain precipitation.
[0047] According to a preferred embodiment of the present invention, the manganese source is selected from at least one of soluble salts of manganese, and the soluble salt of manganese may be, for example, manganese nitrate, manganese carbonate, manganese chloride, manganese acetate, manganese sulfate, and the like.
[0048] According to a preferred embodiment of the present invention, in solution III, the solvent is selected from at least one of water, ethylene glycol, glycerol and polyethylene glycol. Preferably, the solvent is glycerol, which is beneficial to improving the catalytic performance of the catalyst.
[0049] According to a preferred embodiment of the present invention, solution III and solution I are added to solution II in parallel for contact to obtain precipitation. Preferably, the solvent of solution III is glycerol, and the solvent of solution II is ethylene glycol.
[0050] The third aspect of the present invention provides a use of the catalyst of the present invention in the thioetherification of mercaptans.
[0051] A fourth aspect of the present invention provides a method for thioetherification of mercaptans, the method comprising:
[0052] (1) sulfiding the mercaptan thioetherification catalyst under sulfiding conditions;
[0053] (2) contacting the mercaptan-containing raw material with a sulfurized mercaptan thioetherification catalyst;
[0054] The mercaptan thioetherification catalyst contains the nickel-iron-aluminum co-precipitation catalyst of the present invention.
[0055] In the present invention, in step (1), conventional vulcanization conditions in the art can achieve the purpose of the present invention. According to a preferred embodiment of the present invention, the vulcanization conditions include: a space velocity of 1.0-5.5 hours -1 .
[0056] According to a preferred embodiment of the present invention, the sulfurization conditions include: the volume ratio of hydrogen to the sulfurizing agent is 100-600:1.
[0057] According to a preferred embodiment of the present invention, the vulcanization conditions include: a vulcanization temperature of 150-400° C. and a vulcanization time of 4-20 hours.
[0058] According to a preferred embodiment of the present invention, the vulcanizing agent is selected from at least one of diethyl disulfide, carbon disulfide, and tert-butyl polysulfide; more preferably, carbon disulfide.
[0059] In the present invention, in step (2), the conventional contact conditions in the art can achieve the purpose of the present invention. According to a preferred embodiment of the present invention, the contact conditions include: a temperature of 80-120°C.
[0060] According to a preferred embodiment of the present invention, the contact conditions include: a pressure of 2.0-3.0 MPa.
[0061] According to a preferred embodiment of the present invention, the contact conditions include: the space velocity of the raw material containing mercaptan is 2-10h -1 , the volume ratio of hydrogen to the mercaptan-containing raw material is 150-250:1.
[0062] In the present invention, the mercaptan-containing raw material can be selected from a wide range. According to a preferred embodiment of the present invention, the mercaptan-containing raw material is selected from at least one of pyrolysis gasoline, pyrolysis diesel and catalyst gasoline. Preferably, the mercaptan content in the mercaptan-containing raw material is 20-600ppm.
[0063] The present invention will be described in detail below through examples.
[0064] In the following examples, the concentration parameters of mercaptan sulfides were determined by GC-SCD.
[0065] In the present invention, the TPR hydrogen atmosphere (H2-TPR) reduction peak temperature test conditions include: H2-TPR uses the AutoChem2920 dynamic adsorption instrument of Micromeritics, USA, with 10 vol.% H2-Ar mixed gas as the reducing gas, the sample amount is 50 mg, the gas flow rate is 50 ml / min, and the sample is heated from room temperature to 800°C at a rate of 10°C / min.
[0066] In the present invention, the particle size of the catalyst is observed by using a transmission electron microscope (TEM), the instrument being JEM-1200EXⅡ of Japan Electronics Co., Ltd. The catalyst surface is peeled off, ground, dispersed in ethanol, and then subjected to ultrasonic dispersion and then placed on a sample net for observation.
[0067] Example 1
[0068] 1500 mL of 1.2 M sodium bicarbonate aqueous solution was used as aqueous solution I; 356 g of nickel nitrate hexahydrate, 297.49 g of ferric nitrate nonahydrate, and 375.13 g of aluminum nitrate nonahydrate were added to 500 mL of ethylene glycol to obtain solution II, and 89 g of manganese nitrate monohydrate was added to 500 mL of ethylene glycol to obtain solution III; solution II and solution III were mixed, heated to 69° C., stirred, and then solution I was added at a rate of 8 mL / min using a syringe pump; after mixing, stirred at 60° C. for 2 hours.
[0069] The precipitate was filtered, washed 3 times using a vacuum filter (300 ml of triple distilled water to wash the precipitate), dried at 105° C. for 48 hours, and the obtained powder was sintered at 450° C. for 3 hours in a muffle furnace to obtain a catalyst. The hydrogen-programmed temperature reduction temperature of the catalyst was 396° C., and the particle size was 2-6 nm.
[0070] Example 2
[0071] 1500 mL of 1.2 M ammonium carbonate aqueous solution was used as aqueous solution I; 523 g of nickel nitrate hexahydrate, 202 g of ferric nitrate nonahydrate, and 375.13 g of aluminum nitrate nonahydrate were added to 500 mL of ethylene glycol to obtain solution II, and 89 g of manganese nitrate monohydrate was added to 500 mL of ethylene glycol to obtain solution III; solution II and solution III were mixed, heated to 69° C., stirred, and then solution I was added at a rate of 8 mL / min using a syringe pump; after mixing, stirred at 60° C. for 2 hours.
[0072] The precipitate was filtered, washed 3 times using a vacuum filter (300 ml of triple distilled water), dried at 105° C. for 48 hours, and the obtained powder was sintered at 450° C. for 3 hours in a muffle furnace to obtain a catalyst. The hydrogen-programmed temperature reduction temperature of the catalyst was 410° C., and the particle size was 4-8 nm.
[0073] Example 3
[0074] 1500 mL of 1.2 M sodium bicarbonate aqueous solution was used as aqueous solution I; 639 g of nickel nitrate hexahydrate, 162 g of ferric nitrate nonahydrate, and 375.13 g of aluminum nitrate nonahydrate were added to 500 mL of water to obtain solution II, and 89 g of manganese nitrate monohydrate was added to 500 mL of water to obtain solution III; solution II and solution III were mixed, heated to 69° C., stirred, and then solution I was added at a rate of 8 mL / min using a syringe pump; after mixing, stirred at 60° C. for 2 hours.
[0075] The precipitate was filtered, washed three times using a vacuum filter (300 ml of triple distilled water), dried at 105° C. for 48 hours, and the resulting powder was sintered at 450° C. for 3 hours in a muffle furnace to obtain a catalyst. The catalyst had a hydrogen-programmed temperature reduction temperature of 423° C. and a particle size of 5-9 nm.
[0076] Example 4
[0077] According to the method of Example 1, except that solution III is not added, specifically: 356g nickel nitrate, 297.49g iron nitrate and 375.13g aluminum nitrate are added to 500mL ethylene glycol to obtain solution II; solution II is heated to 69°C, stirred, and then solution I is added at a rate of 8mL / min using a syringe pump; after mixing, stirring at 60°C for 2 hours; the other conditions are the same as in Example 1. The hydrogen-programmed temperature reduction temperature of the catalyst is 430°C, and the particle size is 5-10nm.
[0078] Example 5
[0079] The method of Example 1 is different in that solution I is directly mixed with the mixture of solution II and solution III, specifically:
[0080] 1500 mL of 1.2 M sodium bicarbonate aqueous solution was used as aqueous solution I; 356 g of nickel nitrate hexahydrate, 297.49 g of ferric nitrate nonahydrate, and 375.13 g of aluminum nitrate nonahydrate were added to 500 mL of ethylene glycol to obtain solution II, and 89 g of manganese nitrate monohydrate was added to 500 mL of ethylene glycol to obtain solution III; solution II and solution III were mixed, heated to 69° C., and stirred, solution I was added to the mixed solution, and after mixing, stirred at 60° C. for 2 hours.
[0081] The precipitate was filtered, washed three times using a vacuum filter (300 ml of triple distilled water), dried at 105° C. for 48 hours, and the resulting powder was sintered at 450° C. for 3 hours in a muffle furnace to obtain a catalyst. The catalyst had a hydrogen-programmed temperature reduction temperature of 440° C. and a particle size of 6-9 nm.
[0082] Example 6
[0083] 1500 mL of 1.2 M sodium bicarbonate aqueous solution was used as aqueous solution I; 356 g of nickel nitrate hexahydrate, 297.49 g of ferric nitrate nonahydrate, and 375.13 g of aluminum nitrate nonahydrate were added to 500 mL of ethylene glycol to obtain solution II, and 236 g of manganese nitrate monohydrate was added to 500 mL of ethylene glycol to obtain solution III; solution II and solution III were mixed and heated to 69° C., stirred, and solution I was slowly added to solution II using a syringe pump (at a rate of 8 mL / min); after mixing, stirred at 60° C. for 2 hours.
[0084] The precipitate was filtered, washed three times using a vacuum filter (300 ml of triple distilled water), dried at 105° C. for 48 hours, and the resulting powder was sintered at 450° C. for 3 hours in a muffle furnace to obtain a catalyst. The catalyst had a hydrogen-programmed temperature reduction temperature of 423° C. and a particle size of 2-6 nm.
[0085] Example 7
[0086] 1500mL of 1.2M sodium bicarbonate aqueous solution was used as aqueous solution I; 356g of nickel nitrate hexahydrate, 297.49g of iron nitrate nonahydrate, and 375.13g of aluminum nitrate nonahydrate were added to 500mL of ethylene glycol to obtain solution II, and 89g of manganese nitrate monohydrate was added to 500mL of glycerol to obtain solution III; solution II was heated to 69°C, stirred, and then solution I was added at a rate of 8mL / min using a syringe pump, and solution III was added at a rate of 6ml / min for parallel flow contact; after mixing, it was stirred at 60°C for 2 hours. The precipitate was filtered and washed 3 times using a vacuum filter (300ml of triple distilled water was used to wash the precipitate), dried at 105°C for 48 hours, and the obtained powder was sintered at 450°C in a muffle furnace for 3 hours to obtain a catalyst. The hydrogen-programmed temperature reduction temperature of the catalyst is 390°C, and the particle size is 2-5nm.
[0087] Embodiment 8-14
[0088] The catalyst powders prepared in Examples 1 to 7 were respectively tableted to a size of 3 mm×3 mm to obtain final finished catalysts;
[0089] The catalysts were evaluated separately:
[0090] (1) Sulfidation conditions: Heat the catalyst to 170°C under hydrogen conditions, switch to H2, H2 flow rate is 200 ml / min, and at the same time add sulfiding agent (DMDS + cyclohexane, S: 5000 ppm), pump flow rate is 1.4 ml / min, and maintain for 10 hours.
[0091] (2) Using a trickle bed reactor, 50 ml of the sulfided catalyst was taken and heated to 2.7 MPa at a temperature of 120°C and a space velocity of 5.5 h for the raw material containing mercaptan. -1 The reaction was carried out under the conditions of hydrogen / oil volume ratio of 250, wherein the raw material containing mercaptan was pyrolysis gasoline and the mercaptan content was 500 ppm. The mercaptan content after the reaction is shown in Table 1.
[0092] Embodiment 15
[0093] The method of Example 8 is followed, except that in step (1), the sulfidation conditions are: the catalyst is heated to 170°C under hydrogen conditions, switched to H2, the H2 flow rate is 200 ml / min, and a sulfiding agent (CS2+cyclohexane, S: 5000 ppm) is added at the same time, the pump flow rate is 1.4 ml / min, and maintained for 10 hours.
[0094] The remaining conditions were the same as those in Example 7; the mercaptan content after the reaction is shown in Table 1.
[0095] Comparative Example 1
[0096] 315g of pseudo-boehmite (with an alumina content of 78%), a binder, etc. were mixed, and then 8g of an aqueous solution containing polyvinyl alcohol (with a mass concentration of 5%) and 180ml of an aqueous solution containing 3.0g of nitric acid were added, and the mixture was squeezed into a clover shape with a diameter of 2.5mm. The wet strips were dried at 50°C for 24 hours and then calcined at 600°C for 4 hours to obtain a catalyst precursor. The catalyst precursor was impregnated with an equal volume of nickel nitrate and ammonium molybdate aqueous solution (the amount of nickel nitrate and ammonium molybdate aqueous solution added was such that the final nickel and molybdenum contents were 10% and 6.5% of the weight of the oxidation catalyst, respectively), dried at 120°C for 4 hours, and calcined at 450°C for 4 hours to obtain an oxidation catalyst C1, with the final nickel and molybdenum contents being 10% and 6.5% of the weight of the oxidation catalyst, respectively. The hydrogen-programmed temperature reduction temperature of the catalyst was 490°C, and the particle size was 8-10nm.
[0097] Comparative Example 2
[0098] The catalyst prepared in Comparative Example 1 was evaluated according to the method of Example 8. The test results are shown in Table 1.
[0099] Table 1
[0100]
[0101]
[0102] It can be seen from the results in Table 1 that, compared with the comparative example, the nickel-iron-aluminum co-precipitation catalyst provided by the present invention has a significantly better effect on desulfurization.
[0103] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A nickel-iron-aluminum co-precipitation catalyst, characterized in that The catalyst comprises the following components: Iron and / or iron oxides, nickel and / or nickel oxides, aluminum and / or aluminum oxides; In terms of element molar ratio, the molar ratio of nickel to aluminum is 0.2-5:1; the molar ratio of iron to aluminum is 0.2-5:1; The hydrogen-programmed temperature reduction temperature of the catalyst is 250-440°C.
2. The catalyst according to claim 1, wherein The molar ratio of nickel to aluminum is 0.5-2:1 based on the molar ratio of the elements; and / or The molar ratio of iron to aluminum is 0.5-2:1, calculated as the molar ratio of the elements; and / or The hydrogen-programmed temperature reduction temperature of the catalyst is 300-440° C.; and / or The catalyst particle size distribution is 2-10 nm.
3. The catalyst according to claim 1 or 2, wherein The catalyst also contains manganese and / or manganese oxide; Preferably, the molar ratio of manganese to aluminum is 0.1-2:1, preferably 0.1-1:1, calculated as the molar ratio of the elements.
4. The method for preparing the catalyst according to any one of claims 1 to 3, characterized in that: The method includes: The aqueous solution I containing alkaline substances is contacted with the solution II containing nickel source, iron source and aluminum source to obtain precipitation, and the precipitation is obtained by separation, washing and drying; and the precipitation is roasted.
5. The preparation method according to claim 4, wherein: The alkaline substance is selected from at least one of sodium bicarbonate, ammonia water, sodium hydroxide, ammonium bicarbonate and sodium carbonate, preferably at least one of sodium bicarbonate and ammonium bicarbonate; and / or In solution II, the solvent is selected from at least one of water, ethylene glycol, glycerol and polyethylene glycol, preferably, the solvent is ethylene glycol; and / or The nickel source is selected from at least one soluble salt of nickel; and / or The iron source is at least one selected from soluble salts of iron; and / or The aluminum source is selected from at least one soluble salt of aluminum.
6. The preparation method according to claim 4 or 5, wherein: In the aqueous solution I, the concentration of the alkaline substance is 0.1-2 mol / L; and / or In solution II, the aluminum source is calculated as aluminum element, and the concentration of aluminum element is 0.1-3 mol / L; and / or Add aqueous solution I into solution II at a rate of 0.2-10 ml / min; and / or The contact conditions include: a temperature of 30-100°C; and / or a time of 40 min-6 h; and / or Drying conditions include: temperature of 80-150°C; and / or time of 2-6h; and / or The calcination conditions include: a temperature of 300-600° C.; and / or a time of 2-6 hours.
7. The preparation method according to any one of claims 4 to 6, wherein: The preparation method of the catalyst also includes: The solution III containing the manganese source, the aqueous solution I and the solution II are contacted to obtain a precipitate, and the precipitate is separated, washed and dried to obtain the precipitate; the precipitate is roasted; preferably, the manganese source is selected from at least one of the soluble salts of manganese.
8. The preparation method according to claim 7, wherein: In solution III, the solvent is selected from at least one of water, ethylene glycol, glycerol and polyethylene glycol, and preferably, the solvent is glycerol.
9. Use of the catalyst according to any one of claims 1 to 3 in the thioetherification of mercaptans.
10. A method for thioetherification of mercaptans, characterized in that: The method includes: (1) sulfiding the mercaptan thioetherification catalyst under sulfiding conditions; (2) contacting the mercaptan-containing raw material with a sulfurized mercaptan thioetherification catalyst; The mercaptan thioetherification catalyst comprises the catalyst according to any one of claims 1 to 3.
11. The method according to claim 10, wherein: In step (1), the vulcanization conditions include: a space velocity of 1.0-5.5 hours -1 ; and / or The volume ratio of hydrogen to sulfiding agent is 100-600:1; and / or The vulcanization temperature is 150-400°C and the vulcanization time is 4-20 hours; Preferably, the vulcanizing agent is selected from at least one of diethyl disulfide, carbon disulfide and tert-butyl polysulfide, more preferably carbon disulfide.
12. The method according to claim 10 or 11, wherein: The mercaptan-containing raw material is selected from at least one of pyrolysis gasoline, pyrolysis diesel and catalytic gasoline. Preferably, the mercaptan content in the mercaptan-containing raw material is 20-600 ppm; and / or In step (2), the contact conditions include: a temperature of 80-120° C.; and / or Pressure is 2.0-3.0MPa; and / or The space velocity of the raw material containing mercaptan is 2-10h -1 , the volume ratio of hydrogen to the mercaptan-containing raw material is 150-250:1.
